Population-based cohort study to investigate the changes in prevalence, severity profile, and treatment modalities used in Korean atopic dermatitis patients - Hyun Ji Lee; Hyun Ju Oh; Gyu Na Lee; Kyung Do Han; Ji Hyun Lee; Young Min Park (Scientific Reports, 2024)
Abstract In this retrospective study spanning from 2002 to 2019, we analyzed data from 355,277 Korean patients diagnosed with atopic dermatitis (AD) through the National Health Insurance System. Our objective was to comprehensively analyze the trends in prevalence, severity profiles, and treatment approaches for AD in Korea over this 18-year period. Initially, AD prevalence stood at 3.88% in 2002 but notably rose to 5.03% by 2019. During the same period, while AD prevalence decreased in the 0–1-year-old group (from 34.52% to 24.83%), it remained relatively stable in the 1–11-year-old group. Conversely, the 12–19-year-old and 20 years or older age groups witnessed substantial increases in AD prevalence, climbing from 2.55 to 6.02% and 1.44% to 3.53%, respectively. Moreover, the proportion of patients classified as having moderate to severe AD grew from 30.96 to 39.78%. Surprisingly, the prescription pattern, predominantly based on corticosteroid administration, exhibited minimal change despite the rising prevalence of moderate and severe AD cases. These findings underline a persistent reliance on corticosteroid-based treatments for AD, even as the condition's severity escalates among Korean adolescents and adults. Consequently, there is a pressing need to develop novel treatment guidelines emphasizing biologics that offer enhanced safety and efficacy.